Blockgletscherabflüsse im Äußeren Hochebenkar: Hydrologie, Wasserchemie und Kieselalgen - Nickus, U.; Krainer, K.; Thies, H.; Tolotti, Monica (Innsbruck university press, 2015)
Hochebenkar rock glacier is one of the most intensively investigated active rock glaciers of the Austrian Alps with first measurements of flow velocities by Pillewizer in 1938. Since 2007 the discharge of the rock glacier outflows has been studied quantitatively by automatic gauges and chemical analysis is used to determine the water quality of the discharge. Runoff of an active rock glacier reveals a high seasonal variability with varying contributions of snowmelt, precipitation events, groundwater and melting of the internal ice body. Peak values of runoff generally occur in late spring caused by the melting of the seasonal winter snow pack. The major melt phase is characterised by a high daily course of runoff values with maxima at night and minima in the late morning. Cold spells generally interrupt the melt phase several times a year causing runoff and its daily course to decrease. Secondary peaks are linked to summer precipitation events when quickflow causes runoff to increase. By late summer or fall, runoff generally decreases and often ceases in November when air temperatures fall below zero.Solute concentrations tend to increase between the onset of major snowmelt and fall. Electrical conductivity – as a measure of the total ion content of a solution – varies from about 100 µS/cm in early summer to some 400 µS/cm in fall at the automatic gauge run by the Hydrographic Service of Tyrol (2,220 m). Conductivity values may even be higher and reach > 500 µS/cm when measured directly at the rock glacier outflow. Heavy summer precipitation events cause a dilution of the highly concentrated rock glacier streams, and secondary runoff peaks coincide with conductivity minima. The same accounts for those ions that dominate the ion content of the brooks, i.e. sulfate, calcium and magnesium. The seasonal course of the solute concentrations reflects the varying contributions of snowmelt, precipitation, groundwater and melting of the internal ice body. So called reference brooks, i.e. brooks without any impact of an ...